EFFECT OF DIETARY SUPPLEMENTATION OF MIACLOST ON PERFORMANCE AND GUT MORPHOLOGY IN BROILER CHICKENS CHALLENGED WITH ESCHERICHIA COLI - M’SADEQ, S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was aimed to investigate the efficacy of MiaClost (Bacillus subtillis PB6 and Enterococuss faecium) as an alternative to antibiotic (zinc bacitracin) on performance and gut health of broiler chickens under Escherichai coli (E. coli) challenge model. A feeding study was conducted using 240-day-old Ross 308 chicks that were randomly assigned to 5 treatments each with 4 replicates and reared in two different rooms. Four treatments including (positive control, antibiotic, MiaClost 1 and MiaClost 2 ) were challenged with E. coli and reared in room1, however the fifth treatment was used as Negative control (nonchallenged) and reared  in the second room. Birds were challenged with E. coli at day 8 and 9 of age. On days 24 and day 35 of birds age, the live body weight was lower (P < 0.01) and feed conversion ratio was higher (P < 0.01) in positive control birds than that of other experimental groups. Both levels of MiaClost significantly increased live body weight over other treatments. Birds in negative control, antibiotic, MiaClost 1 and MiaClost 2 increased villus height (P > 0.03) and increased villus height/ crypt depth ratio (P > 0.04) in compare to positive control. Furthermore, the serum concentration of alanine transaminase (ALT) was significantly lower (P < 0.001) in negative control and MiaClost 2 supplemented birds compared to positive control, antibiotic and MiaClost 1. The highest concentration of glucose was observed in the serum of positive control. In this study the MiaClost was as effective as antibiotic in preventing the expression of the negative impacts of E. coli on the performance and gut health of broiler chickens. This study indicates that MiaClost has promise as a tool for controlling E. coli in broiler production.